2020
DOI: 10.1101/2020.04.24.059618
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fractal analysis of muscle activity patterns during locomotion: pitfalls and how to avoid them

Abstract: Time-dependent physiological data, such as electromyogram (EMG) recordings from multiple 15 muscles, is often difficult to interpret objectively. Here, we used EMG data gathered during mouse locomotion to investigate the effects of calculation parameters and data quality on two metrics for fractal analysis: the Higuchi's fractal dimension (HFD) and the Hurst exponent (H).A curve is fractal if it repeats itself at every scale or, in other words, if its shape remains unchanged when zooming in the curve at every … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…To assess the local complexity [44] of motor primitives, we calculated the Higuchi's fractal dimension (HFD), assuming that these time series exhibit self-affinity properties [11,20,21,[45][46][47][48]. Following the procedure first described by Higuchi [20], for each motor primitive H(t)[H (1), 455 H(n)], k sets of new time series must be constructed, where k is an integer interval time and 2 < k < k max :…”
Section: Higuchi's Fractal Dimension Of Motor Primitives 29mentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the local complexity [44] of motor primitives, we calculated the Higuchi's fractal dimension (HFD), assuming that these time series exhibit self-affinity properties [11,20,21,[45][46][47][48]. Following the procedure first described by Higuchi [20], for each motor primitive H(t)[H (1), 455 H(n)], k sets of new time series must be constructed, where k is an integer interval time and 2 < k < k max :…”
Section: Higuchi's Fractal Dimension Of Motor Primitives 29mentioning
confidence: 99%
“…For each trial, the HFD 465 of the primitives obtained by NMF was calculated separately and then averaged, so that each trial ultimately consisted of one HFD value [11]. Following suggestions from previous studies, k max was chosen as the most linear part of the log-log plot, which in our data led us to choose k max = 10 [48,49].…”
Section: Higuchi's Fractal Dimension Of Motor Primitives 29mentioning
confidence: 99%
“…Then, we analyzed the motor modules, or the weighted contributions of each muscle activity, and the timing characteristics of motor primitives, which are the time-dependent components of muscle synergies (Santuz et al, 2018a). Lastly, we used fractal analysis to compute the Hurst exponent of motor primitives, in order to gain deeper insight into their temporal structure (Santuz and Akay, 2020). By using these tools, we recently found that both internal and external perturbations applied to human and murine locomotion affect the timing of motor primitives, despite minor changes in the number and composition of motor modules (Santuz et al, 2018a(Santuz et al, , 2019(Santuz et al, , 2020aSantuz and Akay, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, we used fractal analysis to compute the Hurst exponent of motor primitives, in order to gain deeper insight into their temporal structure (Santuz and Akay, 2020). By using these tools, we recently found that both internal and external perturbations applied to human and murine locomotion affect the timing of motor primitives, despite minor changes in the number and composition of motor modules (Santuz et al, 2018a(Santuz et al, , 2019(Santuz et al, , 2020aSantuz and Akay, 2020). Specifically, we could systematically associate a relatively longer duration of motor primitives (i.e., increased width of the signal) in genetically modified mice lacking proprioceptive feedback from muscle spindles (Santuz et al, 2019), in aging humans as compared to young (Santuz et al, 2020a), and in young adults walking and running on uneven terrain (Santuz et al, 2018a), on unstable ground (Santuz et al, 2020a), or running at extremely high speeds (Santuz et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation